Does robot-assisted gait training improve ambulation in highly disabled multiple sclerosis people? A pilot randomized control trial. (April 2017) - Pompa, Alessandra; Morone, Giovanni; Iosa, Marco; Pace, Luca; Catani, Sheila; Casillo, Paolo; Clemenzi, Alessandro; Troisi, Elio; Tonini, Angelo; Paolucci, Stefano; Grasso, Maria Grazia
Background: Robotic training is commonly used to assist walking training in patients affected by multiple sclerosis (MS) with non-conclusive results. Objective: To compare the effect of robot-assisted gait training (RAGT) with that of conventional walking training (CWT) on gait competencies, global ability, fatigue and spasticity in a group of severely affected patients with MS. Methods: A pilot, single-blind randomized controlled trial was conducted in 43 severe (Expanded Disability Status Scale (EDSS) score of 6–7.5) and non-autonomous ambulant in-patients with MS. Experimental group performed 12 sessions of RAGT, whereas control group performed the same amount of CWT. Primary outcome measures were gait ability assessed by 2 minutes walking test and Functional Ambulatory Category; secondary outcomes were global ability (modified Barthel Index), global mobility (Rivermead Mobility Index), severity of disease (EDSS) and subjectively perceived fatigue (Fatigue Severity Scale). Results: The number of subjects who achieved a clinical significant improvement was significantly higher in RAGT than in CWT ( p  < 0.05 for both primary outcome measures). RAGT also led to an improvement in all the other clinical parameters (global ability: p  < 0.001, global mobility: p  < 0.001, EDSS: p  = 0.014 and fatigue: p  = 0.001). Conclusions: RAGT improved the walking competencies in non-autonomous ambulant patients with MS, with benefits in terms of perceived fatigue.